The use of experimental activities as a resource for environmental education: a case of water reuse at school (Research, Society and Development, 2021)
With the increase in water waste and pollution of the environment, human activity has become a major generator of waste, causing numerous environmental consequences. The scarcity of water resources is one of the main consequences found in our current scenario. In view of the scarcity of water, several alternative actions for the treatment of wastewater are being developed. One technique that can favor the decontamination of water is electroflocculation, which causes the agglutination of impurities through oxidation reactions. Based on this assumption, the main objective of this work is to analyze how the development of experimental activities in the teaching of chemistry can promote awareness for the preservation of water resources. The research included 28 students enrolled in the 2nd grade of high school at a state public school in Colatina-ES in 2019, presenting a methodology with a qualitative and experimental approach. The data were analyzed using the Observational Analysis Method, allowing us to conclude that the use of experimentation in the teaching process when linked to Environmental Education can generate incentives to curiosity and research, enhancing knowledge of the relationship between man and the environment.